2011
DOI: 10.1287/isre.1100.0286
|View full text |Cite
|
Sign up to set email alerts
|

Research Note—Knowledge Exploration and Exploitation: The Impacts of Psychological Climate and Knowledge Management System Access

Abstract: galletta@katz.pitt.edu} F irms need to balance efficiency gains obtained through exploiting existing knowledge assets with long-term competitive viability achieved through exploring new knowledge resources. Because the use of knowledge management systems (KMSs) continues to expand, understanding how these systems affect exploration and exploitation practices at the individual level is important to advance both knowledge management theory and practice. This study reports the results of a multi-industry survey i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 53 publications
2
94
0
Order By: Relevance
“…Considerable research has identified the organizational context as an important moderating factor in the relationship between IS use and performance (Burton-Jones and Straub, 2006;Jasperson et al, 2005). Therefore, when studying potential relationships between IT use and individual performance, it is important to take the working environment's characteristics into account (e.g., Durcikova et al, 2011;Leonardi and Barley, 2010). Although contextual factors are important for understanding behavioral phenomena, they have received limited attention in organizational research (e.g., Johns, 2006;Li et al, 2013;Orlikowski and Iacono, 2001;Venkatesh et al, 2011).…”
Section: The Moderating Role Of Task Equivocalitymentioning
confidence: 99%
“…Considerable research has identified the organizational context as an important moderating factor in the relationship between IS use and performance (Burton-Jones and Straub, 2006;Jasperson et al, 2005). Therefore, when studying potential relationships between IT use and individual performance, it is important to take the working environment's characteristics into account (e.g., Durcikova et al, 2011;Leonardi and Barley, 2010). Although contextual factors are important for understanding behavioral phenomena, they have received limited attention in organizational research (e.g., Johns, 2006;Li et al, 2013;Orlikowski and Iacono, 2001;Venkatesh et al, 2011).…”
Section: The Moderating Role Of Task Equivocalitymentioning
confidence: 99%
“…Two key, yet distinct, post-acceptance IS usage behaviors that employees can engage in to achieve work objectives are (1) routine use (RTN), or using IS in a routine and standardized manner to support their work (Saga andZmud 1994, Schwarz 2003), and (2) innovative use (INV), or applying IS innovatively to support their work (Ahuja andThatcher 2005, Jasperson et al 2005). Routine and innovation behaviors have been shown to create significant advantages when they coexist in various organizational behavior contexts including the following: employees' simultaneous pursuit of standard performance and innovative performance (Janssen 2001, Katz andKahn 1966), knowledge workers' reuse of existing solutions and exploration of new solutions to solve problems (Durcikova et al 2011), customers' general and innovative product usage behaviors (Hirschman 1980, Ridgway andPrice 1994), and organizations' use of both exploitation and exploration learning strategies (e.g., Atuahene-Gima and Murray 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The decreasing effect of the direct influence of CIO leadership to firm IT knowledge may be explained by referring to Mintzberg [39], who classified employees not as subordinates of the CIO, but as followers of the TMT, even in cases of IT issues. Referring to the concept of organizational climates as prescription of behavioral and attitudinal mindsets [62,31,20], we expect knowledge leaders to be legitimized and empowered by other C-level leaders [1]. The full mediation effect for H3 suggests, that this is not the case in our sample: The CIO leadership does not di- 0.244 * rectly influence firm IT knowledge.…”
Section: Resultsmentioning
confidence: 83%
“…Closely related to the concept of organizational culture, organizational climates prescribe the transformation of the rather permanent and enduring cultures into behavioral and attitudinal mindsets [62,31,20]. Organizational cultures are defined as shared sets of common values, understandings, and beliefs [30,55].…”
Section: Organizational Climatementioning
confidence: 99%